Decision-making throughout the whole process of relapse: a qualitative analysis of problem drinkers' accounts of recent episodes. (October 2013) - Takeda, Yuko; Roper, Louise; Duff, Simon; Booth, Peter G.
<x xml:space="preserve">Abstract</x> Background & Aims: Models of relapse have usually focused on the antecedents to a drinking session. This qualitative study examined themes within the whole process of relapse in alcohol use (including four phases: before, during, ending and following a drinking session). Methods: Fifteen clients from a UK alcohol treatment clinic received a semi-structured interview, and in-depth accounts of their most recent relapse experiences were obtained. Interview transcripts were analysed using thematic analysis. Results: Participants made sense of their relapse as being caused by circumstantial and compelling triggers, over which they perceived having little control. However, less readily identified, the whole process of relapse was underpinned by a sequence of ordinary decisions. Participants selected options in beverage choice, purchasing and drinking behaviour, which minimised anticipated negative outcomes of a relapse. Their continued drinking was reinforced by primary and secondary gains, and beliefs of uncontrollability. Participants were able to stop drinking, without assistance, when they had enough. Negative consequences of relapse were delayed and less serious than drinkers anticipated. Sharing their accounts with supportive others gave them a sense of consolation. Conclusions: Reflecting on the whole process of relapse and building up drinkers' sense of control may be important components of relapse prevention.